Diverse data structures applied in the creation of console games as a result of a discipline’s assessment project - Ascari, Rúbia Eliza de Oliveira Schultz; Fávero, Eliane Maria De Bortoli (Anais do Simpósio Brasileiro de Educação em Computação (EDUCOMP); 2025: Anais do V Simpósio Brasileiro de Educação em Computação, 2025)
Project development is commonly used to assess disciplines in higher education courses linked to Computer Science. Data Structure is a subject of great importance for courses in this area, however, its contents are often considered complex and tedious by students. Looking for an attractive alternative to partially assess the students of a Data Structure 2 discipline of a Technology in Systems Analysis and Development course, a game-based approach was used for final project development. The students developed simple games, with interaction via console, using C program language and at least one of the Data Structures studied. Results are briefly described in this paper, and the hope is that sharing the creativity displayed by students could be helpful to educators.